The effect of pressing needle therapy on depression, anxiety, and sleep for patients in convalescence from COVID-19 - Liang, Ruilong; Tang, Lin; Li, Lutong; Zhao, Na; Yu, Xintong; Li, Jinjin; Wang, Qianqian; Cun, Haifeng; Gao, Xiaolin; Yang, Wenjia (Frontiers in Neurology, 2024)
ObjectiveTo evaluate the effect of pressing needle therapy on depression, anxiety, and sleep in patients recovering from COVID-19, and to provide a more effective and convenient treatment for the sequelae of COVID-19.MethodsA total of 136 patients recovering from COVID-19 were randomized into a treatment group (68 cases) and a control group (68 cases, with one case dropping out). The treatment group received pressing needle therapy, while the control group received sham pressing needle therapy, three times a week for 4 weeks. The Patient Health Questionnaire (PHQ-9), Generalized Anxiety Disorder Scale (GAD-7), and Insomnia Severity Index (ISI) were used to evaluate patients’ emotional states and sleep quality. These scales were assessed before, after, and at a 1-month follow-up.ResultsCompared to before treatment, the treatment group showed a significant decrease in PHQ-9 scores (p < 0.05, Cohen’s d = 1.26), GAD-7 scores (p < 0.05, Cohen’s d = 1.10), and ISI scores (p < 0.05, Cohen’s d = 0.94) after treatment. Similarly, at the 1-month follow-up, significant decreases were observed in PHQ-9 scores (p < 0.05, Cohen’s d = 1.11), GAD-7 scores (p < 0.05, Cohen’s d = 0.88), and ISI scores (p < 0.05, Cohen’s d = 0.94). In contrast, the control group demonstrated no statistically significant differences in PHQ-9, GAD-7, or ISI scores after treatment or at the 1-month follow-up (p > 0.05). Between the two groups, statistically significant improvements (p < 0.05) were observed in PHQ-9 scores (Cohen’s d = 1.47), GAD-7 scores (Cohen’s d = 1.61), and ISI scores (Cohen’s d = 1.06) after treatment. At the 1-month follow-up, statistically significant differences (p < 0.05) between the two groups were also noted in PHQ-9 scores (Cohen’s d = 1.10), GAD-7 scores (Cohen’s d = 0.87), and ISI scores (Cohen’s d = 0.92).ConclusionPressing needle therapy significantly improves the mental health and sleep quality of patients recovering from COVID-19. It enhances their quality of life, promotes early recovery, and is simple and easy to administer, making it a treatment worthy of clinical application.Clinical trial registrationhttps://www.chictr.org.cn/.